Mechanophilia – a case report of a specific fetishistic disorder - Osvath, Peter; Könczöl, Franciska; Fekete, Sándor; Tényi, Tamás (Frontiers in Psychiatry, 2026)
In our case report, we present a very rare variant of fetishism, mechanophilia, by describing a case from our forensic psychiatric practice. Mechanophilia is a form of fetishism classified as a paraphilia, when a person is sexually aroused by various vehicles, most often cars, less often bicycles or airplanes. We report on the forensic psychiatric examination of a middle-aged man, who opened the fuel filler openings of cars parked in the yard of a car service, then smeared a substance of unknown origin into the tank and then performed a sexual act by placing his genitals in the filling openings. Our examination confirmed a sexual disorder, fetishism (including mechanophilia), which developed in addition to mild intellectual disability (IQ:66) - classified as a paraphilia.